Married Dispensation in Pressing Efforts of Divorce Numbers - Abdul Mutalip; Rozihan Rozihan (Law Development Journal, 2020)
The purpose of this study is to determine the factors and judges' considerations that influence the application for the grant of dispensation of marriage, as well as the role of dispensation of marriage in an effort to reduce the divorce rate. The research method used is juridical-sociological, juridical, which discusses research using laws and regulations related to marriage dispensation. The sociological approach is used to find out and understand how the judge's consideration factors in granting a marriage dispensation request. From the results of the study concluded that the factors causing the submission of applications for dispensation of marriage include pregnancy outside of marriage, concerns of parents about their children, economic factors and educational factors. The basis for the judge's consideration in granting dispensation to marriage is that there is no prohibition on marriage, physical, mental, biological, sociological and financial maturity in a state of urgency (pregnancy out of wedlock) the desire/agreement of both parties. While efforts to dispensate marriage in an effort to reduce the divorce rate are not yet certain, it can actually increase the divorce rate due to the unstable mental and psychological stability of children in fostering a household.